PENGEMBANGAN TEKNOLOGI LASER SEBAGAI BIOSTIMULATOR UNTUK PENGGEMUKAN DAN PEMATANGAN TELUR KEPITING BAKAU (Scylla serrata) - Pungky Slamet Wisnu Kusuma; Dyah Hariani; Akhmad Taufiq Mukti; Maria A gustini (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
Mud crab was one of the fisheries commodities that havea high economic prospect and good market opportunity, local and export. Soft Laser technology could be achieved using He-Ne and Diode as biostirnulator for fattening, egg maturation stage and duration of mud crab. This research was application experimental that used to Factorial Complete Random Design with treatment laser with wavelength differences (632,8 nm and 635 nm) and Factor II: Control or no treatment, shooted in theeyestalk point (M) and shooted in reproduction point (R) with l O replication. The result of this study indicated that utilization soft laser influence growth and egg maturation stage and duration of mud crab. Treatment shooted laser He-Ne (LI) to produce growth and egg maturation stage and duration of mud crab was betterthan not shooted laser. Treatment shooted soft laser He-Ne (LI) at the eyestalk point to produce better growth as 1,8393 gram and egg maturation stage and duration of mud crab was highest, to produce 2 egg maturation stage of full stage as 4 crabs of9 crabs reached stadia two (LI) with duration of egg maturation means 9,88 ± 2, 15 days and control (1,2233 to growth and egg maruration stage reached 3 crabs to 2 full stage of 7 crabs with duration means 17,33±4,42days).